Advances in Grape and Wine Biotechnology 2019
DOI: 10.5772/intechopen.86443
|View full text |Cite
|
Sign up to set email alerts
|

Somatic Variation and Cultivar Innovation in Grapevine

Abstract: Paradoxically, continuous vegetative multiplication of traditional grapevine cultivars aimed to maintain cultivar attributes in this highly heterozygous species ends in the accumulation of considerable somatic variation. This variation has long contributed to cultivar adaptation and evolution under changing environmental and cultivation conditions and has also been a source of novel traits. Understanding how this somatic variation originates provides tools for genetics-assisted tracking of selected variants an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
30
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(31 citation statements)
references
References 86 publications
(134 reference statements)
1
30
0
Order By: Relevance
“…'Uva Rey' showed a very high density unlike 'Mantuo de Pilas' with a very low one. Similar phenotypic differences have been found between other cultivars such as 'Garnacha' and 'Garnacha Peluda' [47], both considered as somatic variants.…”
Section: Discussionsupporting
confidence: 78%
“…'Uva Rey' showed a very high density unlike 'Mantuo de Pilas' with a very low one. Similar phenotypic differences have been found between other cultivars such as 'Garnacha' and 'Garnacha Peluda' [47], both considered as somatic variants.…”
Section: Discussionsupporting
confidence: 78%
“…Belaj et al [ 62 ] suggested that multiple bands for UDO43 may be the amplification products of two different loci. In this sense, we only found one genotype with three alleles at this locus ( Table S4 ) and it could also be due to mosaicism, a phenomenon more frequent during the senescent phase of a tree, which can accumulate mutations without phenotypic consequences [ 20 , 63 , 64 , 65 ].…”
Section: Discussionmentioning
confidence: 99%
“…In fact, until its unique phenotypic and agronomic features are clearly distinguished, a different genotype will not be considered to be a new cultivar (International Union for the Protection of New Varieties of Plants, 1991 in [ 20 ]). The number of somatic mutations appearing in a given variety is expected to increase proportionally with its age (the investigated trees were centuries-old) and cultivation area and some genotypes could be more prone to generate somatic variants [ 65 ]. Molecular variants have been commonly reported also in other olive cultivars widely cultivated in different areas, as well as in ancient and antique cultivars grown throughout history (i.e., ‘Ogliarola di Lecce’, ‘Ogliarola Barese’, ‘Ogliarola Garganica’, ‘Biancolilla’, ‘Giarraffa’, ‘Moresca’ (Italy), ‘Picholine Marocaine’ (Morocco), ‘Cirujal’, ‘Farga’, ‘Lechin de Granada’, ‘Verdial de Velez Malaga’ (Spain); [ 17 , 20 , 21 , 31 , 32 , 34 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In perennial plant species, where mutants are difficult to generate and to screen, natural somatic variants represent a unique resource to understand the genetic control of target traits, because they result from the effect of single mutation or epimutation events in a given genetic background [70][71][72][73].…”
Section: Reasons and Tools For Investigating New Seedlessness Sourcesmentioning
confidence: 99%